2011
DOI: 10.1021/jp2057805
|View full text |Cite
|
Sign up to set email alerts
|

Populations of Carbonic Acid Isomers at 210 K from a Fast Two-Electron Reduced-Density Matrix Theory

Abstract: Parametrization of the 2-electron reduced density matrix (2-RDM) rather than the many-electron wave function yields a new family of electronic-structure methods that are faster and more accurate than traditional coupled electron-pair methods including coupled cluster with single and double excitations. Deriving the parametrization from N-representability conditions generates a 2-RDM that captures significant correlation from triple and higher-order excitations at the cost of double excitations. We apply the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…Yet, the exact crystal structure of β -H 2 CO 3 is still unknown. The FT-IR and Raman spectra of solid H 2 CO 3 below 220 K at low pressure are now well established and several theoretical studies have reported on the structure and stability of H 2 CO 3 with respect to decomposition to CO 2 and H 2 O as well as on the relative stability of its isomers and on their vibrational characteristics 7 8 13 14 15 . Its molecular decomposition rate has been investigated both experimentally 16 and theoretically and it was found to be accelerated over 10 12 times at ambient conditions by as few as three water molecules to reach macroscopically observed decomposition rates 1 17 .…”
mentioning
confidence: 99%
“…Yet, the exact crystal structure of β -H 2 CO 3 is still unknown. The FT-IR and Raman spectra of solid H 2 CO 3 below 220 K at low pressure are now well established and several theoretical studies have reported on the structure and stability of H 2 CO 3 with respect to decomposition to CO 2 and H 2 O as well as on the relative stability of its isomers and on their vibrational characteristics 7 8 13 14 15 . Its molecular decomposition rate has been investigated both experimentally 16 and theoretically and it was found to be accelerated over 10 12 times at ambient conditions by as few as three water molecules to reach macroscopically observed decomposition rates 1 17 .…”
mentioning
confidence: 99%
“…We calculated the energies of bicyclobutane, gauche-1,3-butadiene, and two transition states using the K and M p2-RDM methods [25][26][27][28][29][30][31][32][33] as well as six wave function methods: Hartree-Fock, configuration interaction with single and double excitations (CISD), coupled cluster with single and double excitations (CCSD), 22,23,58 coupled cluster with a correction for triple excitations [CCSD(T)], 23 completely renormalized coupled cluster [CR-CC(T)], 23,24 and coupled cluster with single, double, and full triple excitations (CCSDT). 59,60 Additionally, characterization was performed with CASSCF (10 electrons, 10 active orbitals) and second-order multireference perturbation theory (MRPT2).…”
Section: A Methodologymentioning
confidence: 99%
“…Parametric 2-RDM methods can be used to obtain 2 D directly without the N-particle wave function. [25][26][27][28][29][30][31][32][33] In parametric 2-RDM methods, the 2-RDM is parametrized as a functional of its lowest order components. The 2-RDM can be expressed as the sum of two Hermitian matrices,…”
Section: A Energy Functional Without N-representability Conditionsmentioning
confidence: 99%
See 2 more Smart Citations